The resurgence of 'ignorance is women's virtue': 'Leftover women' and constructing 'ideal' levels of female education in China. Issue 8 (17th November 2022) - You, Yun; Nussey, Charlotte
ABSTRACT: This paper considers the construction of an 'ideal' level of female education in China by reflecting on the social phenomenon of 'leftover women', and the perpetuation of this stigma by both Chinese state media. It contributes an in-depth engagement with the educational dimensions of 'leftover women' through innovative discourse analysis that examines the content of one of the most popular Chinese dating shows in the last decade. This analysis reveals the role of 'experts' in preserving myths about being or becoming 'leftover', as well as the influence of family, in particular mothers, on young Chinese women's choices and self-perception. This paper argues that by attending to popular discourses and their reframing of older Chinese ideas, in particular, 'ignorance is women's virtue', we can offer qualitative insights to the relatively lower numbers of Chinese women at doctoral education levels.